Functional nanocomposites for energy storage: chemistry and new horizons - Chen, Shuyang; Skordos, Alexandros A.; Thakur, Vijay Kumar (Elsevier, 2020)
Energy storage devices are one of the hot spots in recent years due to the environmental problems caused by the large consumption of unsustainable energy such as petroleum or coal. Capacitors are a common device for energy storage, especially electrical energy. A variety of types including electrolytic capacitors, mica capacitors, paper capacitors, ceramic capacitors, film capacitors, and non-polarized capacitors have been proposed. Their specific applications depend on their intrinsic properties. Dielectric capacitors have reasonable energy storage density, with current research focusing on the enhancement of energy density and making the materials more flexible as well as lightweight. Improvement strategies are based on the premise that use of two or more different materials (e.g. polymers and ceramics/metals) at an optimal formulation can result in properties that combine the advantages of the precursor materials. Different polymers especially fluoropolymers (e.g. PVDF and PVDF based co-polymer) are the main components in dielectric nanocomposites for capacitors with high energy storage performance. In this article, we have briefly summarized the recent advances in functional polymers nanocomposites for energy storage applications with a primary focus on polymers, surface engineering, functional groups and novel synthesis/manufacturing concepts applied to new materials. The article presents a unique integrated structure and approaches providing key knowledge for the design and development of novel, low-cost, multifunctional next-generation energy storage materials with improved efficiency.
Keywords: Nanomaterials; Energy; Ceramics; Capacitors